Information technology: digital transformation and the tech future - Bohatyrov, Roman (Запоріжжя: ТДАТУ, 2026)
When we talk about digital transformation in 2026, we are not just talking about companies getting faster computers or moving their files to the cloud. In Ukraine, this process has become something much bigger – it is a matter of national resilience. While the rest of the world follows a slow, planned path to digitalization, Ukraine had to jump ten years ahead in just a few. We have turned from an “outsourcing hub” where people just did tasks for Western clients into a “Product Nation” that builds its own unique tech. Today, the world is looking at us to see how a digital state and a digital army actually work under pressure.
Keywords: information technology; digital transformation